GPU-based simulations of fracture in idealized brick and mortar composites. (July 2015) - William Pro, J.; Kwei Lim, Rone; Petzold, Linda R.; Utz, Marcel; Begley, Matthew R.
Abstract: Stiff ceramic platelets (or bricks) that are aligned and bonded to a second ductile phase with low volume fraction (mortar) are a promising pathway to produce stiff, high-toughness composites. For certain ranges of constituent properties, including those of some synthetic analogs to nacre, one can demonstrate that the deformation is dominated by relative brick motions. This paper describes simulations of fracture that explicitly track the motions of individual rigid bricks in an idealized microstructure; cohesive tractions acting between the bricks introduce elastic, plastic and rupture behaviors. Results are presented for the stresses and damage near macroscopic cracks with different brick orientations relative to the loading orientation. The anisotropic macroscopic initiation toughness is computed for small-scale yielding conditions and is shown to be independent of specimen geometry and loading configuration. The results are shown to be in agreement with previously published experiments on synthetic nacre.